The Functional Preparedness Of Football Players With Various Ability - Thuc, Dao Chanh (Innovative Journal of Medical and Health Sciences, 2019)
This study on the functional readiness of football players in the different game roles of the teams of Vietnam’s first and second championships is revealed. The criteria for the readiness of football players are indicators such as maximum oxygen consumption and physical performance. Functional status of the players is determined in the research laboratory of HCM State Physical Culture Academy. The difference in the structure of the functional readiness of the players with different abilities of different playing roles (goalkeeper, center and wing, central midfield and wing and attack) is revealed. Key words: football players–playing role–functional readiness–VO2max–PWC170